Analysis of Corporate Leadership Practices on Performance of Logistics Industry, Dubai, United Arab Emirates - Mbuvi, Charles; Mandere, Evans Nyamboga; Kilei, Peary (The Journal of Accounting and Management, 2025)
Today’s business environment demands systemic, forward-looking, and change-driven corporate leadership. Pragmatic leadership is vital in navigating the volatile, uncertain, complex, and ambiguous conditions of the 21st century. Effective corporate leadership is therefore a key factor for organizational success in this dynamic era. This study analyzed how corporate leadership practices influence performance of the logistics industry in Dubai, UAE. It examined how Dubai’s logistics cluster applies transformational, transactional, laissez-faire, and strategic leadership practices concurrently, to enhance performance. Hierarchical organizational structure was considered as a moderating variable, and treated as a dummy variable in the analysis. The study was guided by Fiedler’s contingency theory, Hersey and Blanchard’s situational leadership theory, and the Path-Goal leadership theory. A cross-sectional and descriptive research design was used, targeting 50 logistics companies, and a population of 700 employees. From this, 70 top, middle, and lower-level managers were selected through stratified random sampling. Data was collected using structured questionnaires and secondary sources. Reliability was confirmed with a Cronbach Alpha above 0.7. Data was analyzed using SPSS-29, through descriptive, inferential, and regression analyses. Results showed that the four leadership practices significantly influenced performance, with an R² of 0.805 and an adjusted R² of 0.770, confirming a strong positive relationship.